Foreign Language Learning Experiences of Deaf and Severely Hard-of-Hearing Czech University Students - Jitka Sedláčková; Edit H. Kontra (Czech Pedagogical Society, 2019)
This paper presents qualitative research on the experiences and opinions of four Czech native speakers learning English as a second language all of whom are either deaf or severely hard-of-hearing and are currently pursuing or have recently finished university studies in the Czech Republic. Within the framework of an international project, the two male and two female respondents were interviewed individually in order to get an insider's perspective on the needs, difficulties and preferred teaching and learning strategies of students with hearing loss. The descriptive-interpretative analysis of the data followed the principles of qualitative research and yielded four main themes: learning experience, motivation, teaching modality, and learning strategies and learner autonomy. The results highlight the importance of learning experience gained in primary and secondary education and the need for teachers who provide positive motivation for deaf learners and are fluent users of Czech Sign Language. The findings can enrich the knowledge of language teachers, teacher trainers as well as language policy makers and are transferable to similar contexts.